Enhanced thermal cracking of VOCs evolved from the thermal degradation of lignin using CO2. (1st April 2016) - Kim, Jieun; Kim, Ki-Hyun; Kwon, Eilhann E.
Abstract: This work offers a mechanistic investigation of the thermal degradation of lignin in the recovery of energy from biomass waste ( i.e., lignin). Particularly, this work describes the influence of CO2 in the pyrolysis process since pyrolysis process has been known as an intermediate step for gasification. This work experimentally justifies the effectiveness of the influence of CO2 in pyrolysis of lignin at temperatures higher than ∼550 °C. Our GC/TOF-MS analysis of pyrolytic oil obtained at temperature lower than ∼500 °C indicated the thermal degradation of lignin via the thermal bond dissociation of phenolic compounds from the macromolecule of lignin: these phenolic compounds identified in the N2 and CO2 environment were nearly identical. The unknown reaction induced by CO2 at temperatures higher than ∼550 °C simultaneously and independently occurred with dehydrogenation of VOCs (volatile organic carbons), which significantly enhanced the generation of CO via providing the additional source of C and O. Thus, this work shows that the ratio of CO to H2 was significantly enhanced in the presence of CO2, the enhancement of which reached up to ∼1000% at 650 °C as compared to the case in N2 . In order to enhance the identified influence of CO2, the porous material ( i.e., activated alumina) was used in pyrolysis of lignin. Our experimental work shows that employing the porous material was indeed effective to enhance the generation of syngas. This observation indirectly implied not only that employing porous materials could enhance the generation of pyrolytic gases, but also that the reaction rate induced by CO2 would be very fast. In summary, this study experimentally justifies the fact that exploiting CO2 as reaction medium enhances not only the thermal efficiency of the thermo-chemical process, but also the sustainability of biomass-derived fuel via achieving the virtuous circle of carbon. Highlights: Enhanced thermal cracking behavior induced by CO2 . Tailoring the ratio of CO to H2 by means of using the different amount of CO2 . Enhanced generation of CO in the presence of CO2 . Simultaneous reaction between CO2 and VOCs at temperatures higher than 550 °C.